The ac Stark shifts of the terahertz clock transitions of barium - 余庚华 耿鹰鸽 李隆 周超 段丞博 柴瑞鹏 杨永明 (Chinese physics B, 2015)
Wavelength-dependent AC Stark shifts and magic wavelengths of the terahertz clock transitions between the metastable triplet states 6s5d3D1 and 6s5d3D2are investigated with considering the optical lattice trapping of barium atoms with the linearly polarized laser. The trap depths and the slopes of light shift difference with distinct magic wavelengths of the optical lattices are also discussed in detail. Several potentially suitable working points for the optical lattice trapping laser are recommended and selected from these magic wavelengths.